(untitled) (PerCursos, 2007)
O artigo apresenta os resultados de uma pesquisa de survey com o público universitário sobre a constituição dos valores modernos na cultura brasileira e o modo de compreensão dos assuntos políticos concernentes ao reconhecimento da dignidade igualitária e à assunção da autenticidade diferencial. A tese de uma modernização individualista no Brasil ancorada na idéia de independência da pessoa moral serve aqui de hipótese teórica para refutar o processo de modernização da interpretação damattiana, pelo menos entre o público universitário. Como conclusão, pode-se sugerir que, no Brasil, a assimilação dos valores da modernidade individualista, que carrega consigo a dimensão da reflexividade moral para julgar sobre ordens de valores subjetivos concernentes às preferências de direitos iguais e de bens culturais, não é orientada segundo valores pré-convencionais, ou seja, valores personalistas. Os critérios de julgamento moral estão estruturados segundo instâncias impessoais do mercado competitivo e da ordem estatal, formando uma lógica de diferenciação e seleção social para o reconhecimento da dignidade e da autenticidade cultural. Palavras-chave: dignidade igualitária; autenticidade diferencial; cultura brasileira; modernização individualista. Abstract: The article presents the conclusion of a survey research on the academic public opinion’s of the modern values constitution in the Brazilian culture realm and the way of comprehend public issues concerning the recognition of equal dignity and the assumption of differential authenticity. The thesis of an individualist modernisation existing in Brazil referred to the idea of the independence of moral person was used as a theoretical hypothesis in order to refute the damatian’s interpretation of the process of modernisation, at least among the academic public. As conclusion, it can be suggested that, in Brazil, the incorporation of individualistic modern values which carries as important the moral reflexivity dimension to judge about some orders of subjectivist values concerning to the preferences of equality of rights and cultural goods is not oriented through pre-conventional values, that is, personal values. The criterions of moral judgement are founded conforming impersonal places of the competitive market and governmental order, which is inducing a logic of social selection and competion to the recognition of the dignity and the cultural authenticity. Key Words: The recognition of equal dignity; the assumption of differential authenticity; Brazilian culture; individualist modernisation.